Extent, spectrum, and predictors of cognitive impairment in urban geriatric population in a district of North India - Priya Keshari; Hari Shankar (Wolters Kluwer Medknow Publications, 2022)
Cognitive impairment (CI) is no longer considered a normal and inevitable change of aging. This study was carried out to assess extent, spectrum, and predictors of cognitive impairment in the participants. A community-based cross-sectional study was done on 616 urban geriatric participants of Varanasi city selected by multistage sampling procedure. The participants were interviewed about their sociodemographic profile using a predesigned and pretested pro forma, and their cognition was assessed through Mini-Mental State Examination tool. Logistic regression analysis was applied for an inferential purpose. Adjusted odds ratios (AORs) and 95% confidence interval were computed. Extent of cognitive impairment in geriatric participants was 22.4%. AORs were maximum in ≥80 years (21.23; 95% Confidence Interval: 7.05-63.94), in illiterate and just literate participants (13.71; 95% Confidence Interval: 6.49-28.98) and in homemakers (17.0; 95% Confidence Interval: 4.28-67.49). Nine out of 40 urban geriatric participants had cognitive impairment. Adversities of cognitive impairment were more with advancing age, nonengagement in gainful employment, and low literacy levels.